Initiation steps towards generating integrated computer supported environment for project-based learning - Basiri, Kouros (Institute of Electrical and Electronics Engineers, 2009)
The advantage of project-based, collaborative assignments has been demonstrated to foster greater depth of learning in traditional classroom settings. However, there are numerous challenges that are inherent within this pedagogy, especially in promoting computer supported collaborative learning. Although lots of computer systems and tools are compatible to support project-based learning (PBL) in a computer supported environment, an integrated computer supported system which provides infrastructure for PBL is still lacking. This paper brings forward the initiative to coalesce and strengthen a set of coherent foundations for generating integrated computer supported environment for PBL by introducing the initiation phase. Understanding the initiation phase activities and their characteristics in computer supported environment is a definite step towards generating an integrated computer supported environment.